Resource Curse or System Failure? Unpacking the Economic, Governance, and Social Dimensions of Khyber Pakhtunkhwa’s Development Trap - Din, Minhaj Ud; Khan, Hamad; Waqas, Muhammad (ACADEMIA International Journal for Social Sciences, 2025)
The Khyber Pakhtunkhwa (KP) province is blessed with natural resources like as extensive forests, mineral riches, a crucial trade route to Central Asia, and hydro power potential of over 30,000 megawatts (MW) and less than one-fifth of the province’s potential mineral value is being mined, and almost every single indication of development is in serious jeopardy. Governance indicators declined sharply between 2010 and 2024, while poverty increased to 48%. Likewise, united districts have shown a multidimensional deprivation of more than 68%. The current research is an interdisciplinary descriptive analysis of the development trajectory of KP. This study seeks to establish whether KP’s low performance is a result of a systemic failure or a normal resource curse. The term “system failure” denotes the disintegration of social structures and the dismemberment of institutions. The research analyzes provincial time series data from official sources (2010-2024) and published qualitative material to highlight changes in extraction, governance, security, poverty and social ramifications. It does not employ causal econometric modeling. Instead, data are acquired using descriptive statistics, year-to-year comparisons, and sociological notions such as social capital, gender norms, informal justice, and route dependency. Results show KP captured less than 20% of the potential mineral value, governance scores fell from 59 to 38, security incidents rose dramatically after 2021, child stunting remained at 42%, citizen trust fell from 55 to 23%, and the share of households using informal justice rose from 18% to 41%. The research suggests that it is more likely to be a failure of institutions and system rather than a conventional resource curse. The analysis concludes that causal conclusions cannot be formed from the given data; instead, it offers descriptive patterns and a costed reform package.